Crossbreeding studies with native Ethiopian beef cattle using imported semen from various breeds - Wagner, D.G.; Holland, G.L.; Mogess, T. (1968)
Presents findings of crossbreeding studies conducted in Ethiopia using frozen semen imported from superior Angus, Hereford, Charolais, St. Gertrudis and Brahman beef bulls, as well as improved Borana zebu bulls; includes data on birth weight, weaning weight, feedlot & slaughter performance, and on disease observations.